Back to the future: lipiodol in lymphography$dfrom diagnostics to theranostics - Pieper, Claus Christian; Hur, Saebeom; Sommer, Christof-Matthias; Nadolski, Gregory; Maleux, Geert; Kim, Jinoo; Itkin, Maxim (Investigative radiology, 2019)
Lipiodol is an iodinated poppy seed oil first synthesized in 1901. Originally developed for therapeutic purposes, it has mainly become a diagnostic contrast medium since the 1920s. At the end of the 20th century, Lipiodol underwent a transition back to a therapeutic agent, as exemplified by its increasing use in lymphangiography and lymphatic interventions. Nowadays, indications for lymphangiography include chylothorax, chylous ascites, chyluria, and peripheral lymphatic fistula or lymphoceles. In these indications, Lipiodol alone has a therapeutic effect with clinical success in 51% to 100% of cases. The 2 main access sites to the lymphatic system for lymphangiography are cannulation of lymphatic vessels in the foot (transpedal) and direct puncture of (mainly inguinal) lymph nodes (transnodal). In case of failure of lymphangiography alone to occlude the leaking lymphatic vessel as well as in indications such as protein-losing enteropathy, postoperative hepatic lymphorrhea, or plastic bronchitis, lymphatic vessels can also be embolized directly by injecting a mixture of Lipiodol and surgical glues (most commonly in thoracic duct embolization). The aim of this article is to review the historical role of Lipiodol and the evolution of its clinical application in lymphangiography over time until the current state-of-the-art lymphatic imaging techniques and interventions.